2023
DOI: 10.1371/journal.pdig.0000189
|View full text |Cite
|
Sign up to set email alerts
|

Beyond high hopes: A scoping review of the 2019–2021 scientific discourse on machine learning in medical imaging

Abstract: Machine learning has become a key driver of the digital health revolution. That comes with a fair share of high hopes and hype. We conducted a scoping review on machine learning in medical imaging, providing a comprehensive outlook of the field’s potential, limitations, and future directions. Most reported strengths and promises included: improved (a) analytic power, (b) efficiency (c) decision making, and (d) equity. Most reported challenges included: (a) structural barriers and imaging heterogeneity, (b) sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 114 publications
0
2
0
Order By: Relevance
“…We have chosen 2016 as the starting year of the review because while it was a year that showed significant advancement in AI, many were concerned about its ethical implications (Mills, 2016 ; Stone et al, 2016 ; Greene et al, 2019 ). Since AI is fast evolving, the literature from the recent years was used to obtain the emergent and most recent results (Nittas et al, 2023 ; Sukums et al, 2023 ). Figure 1 presents our review flowchart following PRISMA's guidelines (Moher et al, 2009 ).…”
Section: Methodsmentioning
confidence: 99%
“…We have chosen 2016 as the starting year of the review because while it was a year that showed significant advancement in AI, many were concerned about its ethical implications (Mills, 2016 ; Stone et al, 2016 ; Greene et al, 2019 ). Since AI is fast evolving, the literature from the recent years was used to obtain the emergent and most recent results (Nittas et al, 2023 ; Sukums et al, 2023 ). Figure 1 presents our review flowchart following PRISMA's guidelines (Moher et al, 2009 ).…”
Section: Methodsmentioning
confidence: 99%
“…While AI-specific challenges, such as limited interpretability and bias risks have been widely discussed, especially in relation to its clinical use 1 , a lesser degree of attention has been paid to issues related to the evidence base supporting the implementation of AI-based applications in the clinical context. Recently, the importance of rigorous testing and real-world validation, including well-designed Randomized Controlled Trials (RCTs), has been emphasized before AI can be integrated into medical practice.…”
Section: Introductionmentioning
confidence: 99%
“…These approaches include various methodologies and techniques that are specifically designed to address the challenges inherent in breast ultrasound image segmentation [13][14][15]. Deep learning (DL) models, predominantly convolutional neural networks (CNNs), have proven remarkable success in accurately segmenting anatomical structures and identifying pathological regions in various medical imaging modalities, including X-ray, MRI, CT, and ultrasound [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%